KARAKTERISTIK KONSELOR PADA CALON KONSELOR BERDASARKAN PERBEDAAN KELOMPOK GENDER - Shinta Mayasari (JURNAL PSIKOLOGI MALAHAYATI, 2020)
ABSTRACT: COUNSELOR CHARACTERISTIC AMONG CANDIDATED COUNSELOR BASED ON GENDER GROUP DIFFERENCES A qualified counselor will determine the success of the counseling process. Three characteristics are needed and determine the quality of a counselor, namely: (1) congruence (authentic), (2) unconditional positive regard (acceptance), and (3) empathy (empathy). This study aims to describe the characteristics of counselors based on gender groups. The research sample consisted of 68 prospective counselor students who were divided into gender groups. The measuring instrument uses a counselor characteristic test developed using controversial statements with alternative Likert scale answers. The results of the study found that there were significant differences in the characteristics of counselors among students of the guidance and counseling study program based on differences in gender groups. There is a significant difference between the need to develop educational programs and effective counselor training for male and female students. The development of congruence characteristics is more needed for male students, while female students on the characteristics of unconditional positive regard. A larger sample size is needed to increase heterogeneity, and additional interviews are conducted individually to deepen the discussion. Key words: counselor characteristics, gender, measurement of emphaty, psychological instrument.  Konselor yang berkualitas akan menentukan keberhasilan proses konseling. Tiga karakteristik yang diperlukan dan menentukan kualitas konselor, yaitu: (1) congruence (otentik), (2) unconditional positive regard (penerimaan), dan (3) empathy (empati). Penelitian ini bertujuan untuk melihat gambaran karakteristik konselor berdasarkan kelompok gender. Sampel penelitian merupakan 68 mahasiswa calon konselor yang dibagi berdasarkan kelompok gender. Alat ukur menggunakan tes karakteristik konselor yang dikembangkan dengan menggunakan pernyataan kontroversial dengan alternatif jawaban skala Likert. Hasil penelitian menemukan ada perbedaan yang signifikan dalam karakteristik konselor pada mahasiswa program studi bimbingan dan konseling berdasarkan perbedaan kelompok gender. Ada perbedaan yang signifikan antara kebutuhan pengembangan program pendidikan dan pelatihan konselor yang efektif bagi mahasiswa laki-laki dan perempuan. Pengembangan karakteristik congruence lebih dibutuhkan untuk mahasiswa laki-laki, sementara mahasiswa perempuan pada karakteristik unconditional positive regard. Jumlah sampel yang lebih besar diperlukan untuk meningkatkan heterogenitas, dan melakukan wawancara tambahan secara individual untuk memperdalam diskusi. Kata kunci: karakteristik konselor, gender, pengukuran empati, instrumen psikologi.